Polyhedral cobalt oxide supported Pt nanoparticles with enhanced performance for toluene catalytic oxidation. (January 2021) - Li, Shuangju; Lin, Yin; Wang, Da; Zhang, Chuanhui; Wang, Zhong; Li, Xuebing
Abstract: Polyhedral CoO x was synthesized by calcination of Co-based metal-organic framework ZIF-67 and highly dispersed Pt nanoparticles were successfully loaded on CoO x . The catalytic results showed that Ptnano /CoO x had the best activity and stability. As compared with conventional Co3 O4, polyhedral CoO x showed more excellent catalytic oxidation performance of toluene, which was related to enhanced oxygen mobility, defective structure and rich active oxygen species provided by Polyhedral CoO x . Moreover, Pt-CoO x metal-support interaction enhanced the dispersion of Pt species and showed more Pt 0 ratio. It was reasonable that the gaseous O2 can be activated directly or moved into the catalyst's surface to form oxygen cycle. Graphical abstract: Image 1 Highlights: Pt supported polyhedral CoO x had the best toluene oxidation activity. The super activity was due to the cooperative action between metal-support. Gaseous O2 was activated or moved into the catalyst's surface to form oxygen cycle.